GDF15-mediated enhancement of the Warburg effect sustains multiple myeloma growth via TGFβ signaling pathway - Wenjing Xue; Ying Li; Yanna Ma; Feng Zhang (Cancer & Metabolism)
Abstract The Warburg effect, characterized by the shift toward aerobic glycolysis, is closely associated with the onset and advancement of tumors, including multiple myeloma (MM). Nevertheless, the specific regulatory mechanisms of glycolysis in MM and its functional role remain unclear. In this study, we identified that growth differentiation factor 15 (GDF15) is a glycolytic regulator, and GDF15 is highly expressed in MM cells and patient samples. Through gain-of-function and loss-of-function experiments, we demonstrated that GDF15 promotes MM cell proliferation and inhibits apoptosis. Moreover, GDF15 enhances Warburg-like metabolism in MM cells, as evidenced by increased glucose uptake, lactate production, and extracellular acidification rate, while reducing oxidative phosphorylation. Importantly, the tumor-promoting effects of GDF15 in MM cells are fermentation-dependent. Mechanistically, GDF15 was found to promote the expression of key glycolytic genes, particularly the glucose transporter GLUT1, through the activation of the TGFβ signaling pathway. Pharmacological inhibition of the TGFβ signaling pathway effectively abrogated the oncogenic activities of GDF15 in MM cells, including cell proliferation, apoptosis, and fermentation. In vivo experiments using a subcutaneous xenotransplanted tumor model confirmed that GDF15 knockdown led to a significant reduction in tumor growth, while GDF15 overexpression promoted tumor growth. Overall, our study provides insights into the molecular mechanisms underlying MM pathogenesis and highlights the potential of targeting GDF15-TGFβ signaling -glycolysis axis as a therapeutic approach for future therapeutic interventions in MM.